The Difference Between Offline and Online Learning During The Pandemic at SMP Muhammadiyah 1 Sidoarjo - Adinda Shafira Ramadhan (International Consortium of Education and Culture Research Studies, 2021)
This research is a qualitative research that aims to explore changes in learning during the Covid-19 pandemic towards learning at SMP Muhammadiyah 1 Sidoarjo. The purpose of this study shows that the impact of the Covid-19 Pandemic on learning includes: (1) Changes from face-to-face learning to online learning; (2) Increasing the use of technology in learning; (3) Increasing student learning independence. This research uses descriptive qualitative method. The results and conclusions of this study are that Covid-19 forces teachers and students to make more use of modern technology in the learning process. teachers and students are required to be able to use devices such as smartphones, computers, tablets and laptops to support online learning.